Vliv silového tréninku na dětský organismus - Strašilová, Kateřina; Vajda, Petr (Masaryk University Press, 2024)
Title in English: The influence of strength training on the children’s body: The influence on selected somatic, physiological and psychological factors Although the strength training of children and adolescents is already often included among the basic building blocks of sports training, many coaches and parents are concerned about the involvement of this type of training in the sports training of their competitors or children. The aim of the publication is to introduce the reader to the basic parameters and recommendations for this type of training for the youth population, to present the effect of strength training on the child's organism and to list the benefits that this training brings.